The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12913-018-3245-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related stigma among people living with HIV/AIDS in rural Central China

Abstract: BackgroundHIV-related stigma among people living with HIV/AIDS (PLWHA) has been associated with many negative consequences, including poor adherence to therapy and undue psychological stress. However, the relative influence of specific demographic and situational factors contributing to HIV-related stigma among rural PLWHA in central China remains unknown. The aim of this study was to explore the level of HIV-related stigma among rural PLWHA across specific demographic and situational factors in central China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 33 publications
6
44
5
2
Order By: Relevance
“…According to this study the prevalence of HIV-related perceived stigma and associated factors among people living with HIV attending Ante-retroviral clinic was lower than the study conducted in Jimma Town was 61.1% (29) and in Nigeria 59.9% (27). The difference might be due to the socio-economical status of the study setting, sample size of the study, the influence of cultural and religious norms of the society.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…According to this study the prevalence of HIV-related perceived stigma and associated factors among people living with HIV attending Ante-retroviral clinic was lower than the study conducted in Jimma Town was 61.1% (29) and in Nigeria 59.9% (27). The difference might be due to the socio-economical status of the study setting, sample size of the study, the influence of cultural and religious norms of the society.…”
Section: Discussioncontrasting
confidence: 54%
“…It was determined by Level of significance (0.05), Power (0.50) with z = 95% confidence internal and the value of ''p'' (p = proportion of prevalence) was taken as prevalence of perceived stigma among People Living with HIV which was found to be 61.1%( done in Jimma town, Ethiopia) (29). Then by adding 10% of non-respondents then, total sample size for this study is 403.…”
Section: Sample Size Determination and Techniquementioning
confidence: 99%
“…Alternatively, while Loutfy et al (2012) found lower stigma scores among patients who attended college, 53 we observed higher HCV‐SS scores among participants who attended some college or earned an associate degree. Several studies among people living with HIV have similarly found increased stigma among those with higher educational attainment 22,54,55 . It is possible that those with higher education may be more attuned to the health‐related and social consequences of their HCV status, and therefore experience greater internalized or perceived stigma.…”
Section: Discussionmentioning
confidence: 99%
“…The estimate bias in our study is likely to be higher with age (see supplementary fig S11), which might lead to underestimation of the actual burden of infectious diseases in adolescents, particularly for HIV/AIDS and other sexually transmitted diseases and bloodborne infections. Because of the social stigma around some sexually transmitted diseases, and lack of health service use for milder gastrointestinal infections, we could have underestimated the burden from these diseases 59. Although more males than females in each age group were not included in the analysis, the percentage of girls not included was larger (17.0% v 19.8%).…”
Section: Discussionmentioning
confidence: 99%